2015
DOI: 10.3762/bjnano.6.61
|View full text |Cite
|
Sign up to set email alerts
|

Overview of nanoscale NEXAFS performed with soft X-ray microscopes

Abstract: SummaryToday, in material science nanoscale structures are becoming more and more important. Not only for the further miniaturization of semiconductor devices like carbon nanotube based transistors, but also for newly developed efficient energy storage devices, gas sensors or catalytic systems nanoscale and functionalized materials have to be analysed. Therefore, analytical tools like near-edge X-ray absorption fine structure (NEXAFS) spectroscopy has to be applied on single nanostructures. Scanning transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…But evidence for effective "bombardment-induced decomposition" (Kelly, 1989) and reduction can even be found in outer space. The low albedo of silicate rocks from the moon's surface was attributed to solar wind bombardment (Hapke, 1973), which causes an enrichment of nanoscale metallic iron particles in the near-surface layer of lunar regolith via a preferential sputtering mechanism, where oxygen is preferentially sputtered off, leaving the reduced bare metal behind (Betz and Wehner, 1983). Whether micrometeoroid impacts have a major contribution to this so-called lunar "space weathering" by (re)melting the surface layer of lunar soil grains or whether solar wind contributes more due to ion (H and He) implantation is still under discussion, however (Kuhlman et al, 2015;Pieters and Noble, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…But evidence for effective "bombardment-induced decomposition" (Kelly, 1989) and reduction can even be found in outer space. The low albedo of silicate rocks from the moon's surface was attributed to solar wind bombardment (Hapke, 1973), which causes an enrichment of nanoscale metallic iron particles in the near-surface layer of lunar regolith via a preferential sputtering mechanism, where oxygen is preferentially sputtered off, leaving the reduced bare metal behind (Betz and Wehner, 1983). Whether micrometeoroid impacts have a major contribution to this so-called lunar "space weathering" by (re)melting the surface layer of lunar soil grains or whether solar wind contributes more due to ion (H and He) implantation is still under discussion, however (Kuhlman et al, 2015;Pieters and Noble, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In fullfield microscopes, e.g. transmission X-ray microscopes (TXM) (Kaulich et al, 2011;Guttmann & Bittencourt, 2015) and X-ray photoemission electron microscopes (X-PEEM) (Gü nther et al, 2002;Leung et al, 2010;Schofield et al, 2014), the whole field of view is directly imaged onto a detector plane so that a spatially resolved imaging detector, such as a CCD or a pixel-array detector, is required. On the other hand, with scanning microscopes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since synchrotron-based X-ray microscopes offer continuously tunable excitation photon energy, it has been shown that within a multilayer of several photoresists consecutively stacked at the same spot, each layer can be addressed separately by the resonant photon energy of the respective Following the development of suitable focusing optics for soft X-rays [49][50][51], the first soft X-ray microscopes were installed in the mid-1980s [52,53]. Since then, STXM has developed into a versatile method for characterization of suitably thin specimens from various scientific disciplines, such as biology, medicine, catalysis, material science, magnetism, geology, cosmology, and cultural heritage [54][55][56][57][58][59][60][61][62][63][64]. Figure 1 depicts a scheme of a modern STXM with all basic elements and their respective degrees of freedom [59,65,66].…”
Section: Introductionmentioning
confidence: 99%